Is daddy coming back in a minute? : explaining (sudden) death in words very young children can understand - Barber, Elke; Barber, Alex, 2005 or 2006- (Jessica Kingsley Publishers, 2016)
Alex and his father are on a boys-only weekend when his father has a heart attack. Alex finds someone to call the ambulance, but his father dies on the way to hospital. His mother comes to get him and explains why his daddy can't come back.